2006
DOI: 10.4319/lom.2006.4.416
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐labeling method for the simultaneous measurement of dissolved inorganic carbon and phosphate uptake by marine planktonic species

Abstract: The measurement of primary production is the foundation for aquatic biogeochemistry research. The biogeochemical cycles of phosphate (P) and other biolimiting elements are tightly linked to marine primary production. We have optimized an existing method of carbon (C) and P dual isotope labeling to study the simultaneous C and P uptake by plankton species in marine environments. The two main objectives of this study were (1) to test the preservation properties of the labeled samples and the calculation methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The methodological problems associated with 24 h incubation experiments can be significant (Nalewajko andGarside, 1983, Harrison andHarris, 1986), especially in terms of losses. However, short incubation experiments should reduce the bias linked to such losses (see discussion in Duhamel et al, 2006). It is important to stress that even if the <0.6 µm fraction is composed of solely heterotrophic bacteria, our data set does not prove that P is turning over at the same rate as the cells.…”
Section: Dip Uptake Rate Measurementsmentioning
confidence: 70%
See 4 more Smart Citations
“…The methodological problems associated with 24 h incubation experiments can be significant (Nalewajko andGarside, 1983, Harrison andHarris, 1986), especially in terms of losses. However, short incubation experiments should reduce the bias linked to such losses (see discussion in Duhamel et al, 2006). It is important to stress that even if the <0.6 µm fraction is composed of solely heterotrophic bacteria, our data set does not prove that P is turning over at the same rate as the cells.…”
Section: Dip Uptake Rate Measurementsmentioning
confidence: 70%
“…P uptake is generally shown to be constant over 24 h (Perry andEppley, 1981, Harrison, 1983;Moutin et al, 2002) but diurnal variations in P uptake have been observed in some studies (Eppley et al, 1971;Harrison et al, 1977;Currie and Kalff, 1984). For the majority of stations, time course experiments for 33 P uptake were linear over 24 h, however there were some variations in P uptake rates at some stations along the BIOSOPE transect (Duhamel et al, 2006). The methodological problems associated with 24 h incubation experiments can be significant (Nalewajko andGarside, 1983, Harrison andHarris, 1986), especially in terms of losses.…”
Section: Dip Uptake Rate Measurementsmentioning
confidence: 99%
See 3 more Smart Citations